Spring Migration and Habitat Use by Seabirds in Eastern Lancaster Sound and Western Baffin Bay - McLaren, Peter L. (ARCTIC, 1982)
The status and distribution, during spring and early summer, of northern fulmars (Fulmarus glacialis), black-legged kittiwakes (Rissa tridactyla), thick-billed murres (Uria lomvia) and black guillemots (Cepphus grylle) were studied during aerial surveys in eastern Lancaster Sound (1976, 1978, 1979) and western Baffin Bay (1978, 1979). Fulmars were present in the study area by early May but most undertook a pre-laying exodus in late May before returning in early June to nest. During June and the first half of July, they were common along coasts and in offshore areas throughout the region. Kittiwakes returned in late May and numbers increased through June, both along coasts and offshore. Numbers offshore decreased after nesting, which begins in mid- to late June. Murres returned to the study area around mid-May and were abundant during June, especially near their colonies. Densities were generally highest along fast ice edges. Guillemots returned to the study area in the last half of May and were widespread along coasts, ice edges and in offshore areas during June. Densities were much lower after nesting, which commences in late June. Densities of fulmars, murres and guillemots were much higher along fast ice edges than along ice-free coasts: the opposite was true of kittiwakes. Offshore, fulmars and kittiwakes preferred waters with little or no pack ice, whereas murres and guillemots preferred moderate to heavy pack ice. These habitat preferences affected the distributions of the species within the region. Ice conditions in eastern Lancaster Sound were markedly different during each of the three years of study. Effects of different ice conditions on the species' distributions are assessed. Seabird distributions in six parts of the region are summarized.Key words: fulmar, kittiwake, murre, guillemot, distribution, habitat use, Lancaster Sound, Baffin Bay